Profile of Nontuberculous Mycobacteria in Patients Suspected of Tuberculosis and Drug-Resistant Tuberculosis - Sharma, Megha; Malhotra, Bharti; Tiwari, Jitendra; Bhargava, Shipra (Journal of Laboratory Physicians, 2020)
Objective Infections due to nontuberculous mycobacteria (NTM) is increasing globally and may present as drug-resistant tuberculosis (DRTB). In India, data on NTM prevalence and species diversity is limited. Present study was conducted to detect the prevalence and profile of NTM among patients suspected of DRTB using paraffin slide culture (PSC)and mycobacteria growth indicator tube (MGIT) culture methods for isolation of NTM.Material and Method A total of 2,938 samples suspected of TB/DRTB were cultured on PSC and MGIT960. Species identification of mycobacterial isolate was done by sequencing of 16s ribosomal RNA gene.Result Among 2938 samples, 35 (1.19%) were found positive for NTM by PSC and 9 (0.30%) were found positive by MGIT. The diversity of NTM species was high (13 species). Out of 35 NTM isolates by PSC, maximum 34.29% (12) isolates were found to be Mycobacterium fortuitum, followed by 11.43% (4) Mycobacterium abscessus and Mycobacterium chelonae, and 42.85% (15) were other species viz. 8.57% (3) were Mycobacterium intracellulare and Mycobacterium kansasii, 5.71% (2) were Mycobacterium peregrinum, and 2.85% (1) were Mycobacterium flavescens, Mycobacterium farcinogenes, Mycobacterium moriokanese, Mycobacterium wolinskyi, Mycobacterium simiae, Mycobacterium goodii, and Mycobacterium terrae each. Coinfection of Mycobacterium tuberculosis(MTB) and NTM was found in 60% (21) samples.Conclusion Prevalence of NTM was low among multidrug resistant tuberculosis/TB suspected patients, similar to other studies done in India. PSC was found better than MGIT for the isolation of NTM, though poor separation of NTM and MTB on subculture may have led to false negativity in cases of coinfection. About 13 species were isolated; M. fortuitum was the most common of all. Since coinfection of NTM and TB can also occur, samples of patients suspected of NTM should be cultured on PSC even if positive for MTB.
Keywords: nontuberculous mycobacteria (NTM); paraffin slide culture (PSC); mycobacterium tuberculosis (MTB)